2021
DOI: 10.1111/nph.17860
|View full text |Cite
|
Sign up to set email alerts
|

The IbBBX24–IbTOE3–IbPRX17 module enhances abiotic stress tolerance by scavenging reactive oxygen species in sweet potato

Abstract: Soil salinity and drought limit sweet potato yield. Scavenging of reactive oxygen species (ROS) by peroxidases (PRXs) is essential during plant stress responses, but how PRX expression is regulated under abiotic stress is not well understood.Here, we report that the B-box (BBX) family transcription factor IbBBX24 activates the expression of the class III peroxidase gene IbPRX17 by binding to its promoter. Overexpression of IbBBX24 and IbPRX17 significantly improved the tolerance of sweet potato to salt and dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 89 publications
(100 reference statements)
1
37
0
Order By: Relevance
“…Accordingly, tolerant species possess a number of ROS detoxifying proteins, such as CAT, POD and SOD, which protect them from oxidative stress (Azevedo-Neto et al 2006). For example, overexpression of IbBBX24 and IbBBX17 in sweet potato improved tolerance to drought and salt stress via scavenging and detoxi cation of ROS (Zhang et al 2022), while transgenic Triticum aestivum overexpressing TaPRX-2A showed increased tolerance to salt as a result of reduced ROS accumulation (Su et al 2020). In this study, overexpression of OsSKL2 in rice reduced H 2 O 2 accumulation and improved the activities of CAT, POD and SOD, thereby enhancing tolerance to drought and salt stress (Fig.…”
Section: Osskl2 Confers To Drought and Salt Stress Via Ros Scavenging...mentioning
confidence: 56%
“…Accordingly, tolerant species possess a number of ROS detoxifying proteins, such as CAT, POD and SOD, which protect them from oxidative stress (Azevedo-Neto et al 2006). For example, overexpression of IbBBX24 and IbBBX17 in sweet potato improved tolerance to drought and salt stress via scavenging and detoxi cation of ROS (Zhang et al 2022), while transgenic Triticum aestivum overexpressing TaPRX-2A showed increased tolerance to salt as a result of reduced ROS accumulation (Su et al 2020). In this study, overexpression of OsSKL2 in rice reduced H 2 O 2 accumulation and improved the activities of CAT, POD and SOD, thereby enhancing tolerance to drought and salt stress (Fig.…”
Section: Osskl2 Confers To Drought and Salt Stress Via Ros Scavenging...mentioning
confidence: 56%
“…Sweet potato ( I. batatas ) is an important food crop; however, its improvement by conventional breeding is limited because its highly heterozygous, generally self-incompatible and outcrossing polyploidy [ 43 ]. Genetic engineering is used to improve the sweet potato [ 5 , 29 , 30 , 31 , 32 ]. The wild ancestor diploid I. trifida acts as an effective resource to improve sweet potato because of its high resistance to abiotic stress [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic and the WT plants were transferred to soils in a greenhouse and then in a field for their evaluation. The cuttings about 25 cm in length were used for further function analysis as described by Zhai et al [ 31 ] and Zhang et al [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations